Free Indirect Discourse in Non-fiction - Stokke, Andreas (Frontiers in Communication, 2021)
This paper considers some uses of Free Indirect Discourse within non-fictional discourse. It is shown that these differ from ordinary uses in that they do not attribute actual thoughts or utterances. I argue that the explanation for this is that these uses of Free Indirect Discourse are not assertoric. Instead, it is argued here that they are fictional uses, that is, they are used with fictional force like utterances used to tell a fictional story. Rather than making assertions about the actual world, these occurrences of Free Indirect Discourse introduce localized fictional scenarios from which audiences are meant to learn factual information. As such, they exhibit some of the ways in which the involvement of perspective in historical fiction has been shown to facilitate learning and retention of information.